Evaluating the Efficacy of Alternative Methodologies to EU and UN SDG Air-Pollution Indicators - Χρόνη, Λαμπρινή (Πανεπιστήμιο Πελοποννήσου, 2024)
Air pollution and air quality are major issues concerning a big part of Earth’s population. In order to address these issues, among others, a global agenda called “Sustainable Development Goals “was established. Under goal 11.6.2 lies a target that implies that countries should reduce the adverse per capita environmental impact of cities, including by paying special attention to air quality and municipal and other waste management. Two approaches by the UN and Eurostat have created two similar indictors, the UN SDG 11.6.2 and the Eurostat sdg_11_50. Both of them examine the annual mean levels of fine particulate matter and are population weighted. Since these approaches are sensitive to the definition of the city, SMURBS suggests a different approach to the indicator, combining EO data and in situ measurements and using objective city definitions. As a result, two indicators arise, using the SMURBS UC approach and the SMURBS FUA approach. The purpose of this study is to test if the SMURBS indicators provide a sufficient alternative approach to the SDG 11.6.2 indicator, and Eurostat sdg_11_50, focusing on European countries and how these are affected by different city definitions.
Αξιολόγηση της Αποτελεσματικότητας Εναλλακτικών Μεθοδολογιών για τους Δείκτες των Στόχων Βιώσιμης Ανάπτυξης για την Ατμοσφαιρική Ρύπανση, της ΕΕ και των Η
Μ.Δ.Ε. 97